Normative Data for Female Adolescents with Eating Disorders on the Multidimensional Anxiety Scale for Children - Watson, Hunna; Hoiles, Kimberley; Egan, Sarah; Limburg, K. (John Wiley & Sons, Inc., 2014)
Objective: To provide normative data on the Multidimensional Anxiety Scale for Children (MASC) for female adolescents presenting for eating disorder (ED) treatment. Method: This study is part of the Helping to Outline Paediatric Eating Disorders Project registry (N ~ 1,000), a prospective ongoing registry study comprising consecutive pediatric tertiary ED referrals. Female adolescents (N=278; 13–17 years) with EDs completed the MASC at intake. Results: Summary data including percentiles are given for the MASC total and subscales. MASC scores were higher than community norms as expected and increased with age (p<.001) and an anorexic spectrum diagnosis (p<.001). Discussion: The norms reported will aid clinicians in the understanding and interpretation of individual MASC scores among female adolescents with EDs and could assist future research to better understand the role of anxiety in the onset and maintenance of EDs.